Exploring the issues and concerns in the implementation of customs trade facilitation initiatives in Central Luzon, Philippines - Mangohig, Joyce Ann V. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
towards liberalization of trade and promoting importation and exportation business. This qualitative study sought to identify the emerging issues and concerns surrounding the implementation of the customs trade facilitation initiatives on exportation and importation in Central Luzon, Philippines. The participants of this study were 300 exporters, importers, and processors of the Port of Limay (Bataan), Port of Subic (Olongapo), and Port of Clark (Pampanga). A written interview guide was used in data collection. Findings showed varied concerns in the customs trade facilitation activities encountered by the participants in the different ports of Central Luzon. Major problems include the issues on processing time, website system, absence of signatories, delayed processes, trade ruling changes, and the absence of the paperless transactions. The preliminary data obtained from this qualitative research may be a baseline for the continuous improvement of the customs trade facilitation activities in the region. A quantitative instrument may likewise be developed based on the merging themes culled from this study to validate this qualitative inquiry's results further. The current study also contributes to the shortage of literature in the Philippines regarding customs trade facilitation initiatives.